1998
DOI: 10.2169/internalmedicine.37.776
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging Findings of the Skeletal Muscle of a Patient with Nemaline Myopathy.

Abstract: This is the first magnetic resonance imaging (MRI) report of nemaline myopathy in which muscle atrophy was not apparent clinically in the lower extremities because of subcutaneous fat. The patient is a 38-year-old womanwhowas admitted to our hospital because of muscle weakness of the four extremities. Until the age of 17 years, she was asymptomatic except that her running speed was slow. The Tx-weighted image of muscle MRIat the mid-thigh level showed hyperintensity of the quadriceps femoris muscle and relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…We observed that the extent of fatty infiltration was negligible for the two groups even though the magnitude was slightly higher in the Neb ‐cKO mice compared with WT. Our results are in line with the small amount of fatty tissue infiltration in the hindlimb muscles ( i.e ., <5%) of two other NEM mouse models, whereas large fat infiltration has been reported in NEM patients . Therefore, our MRI data provide evidence that the Neb ‐cKO mouse model does not reproduce the large fatty infiltration typically observed in NEM patients.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…We observed that the extent of fatty infiltration was negligible for the two groups even though the magnitude was slightly higher in the Neb ‐cKO mice compared with WT. Our results are in line with the small amount of fatty tissue infiltration in the hindlimb muscles ( i.e ., <5%) of two other NEM mouse models, whereas large fat infiltration has been reported in NEM patients . Therefore, our MRI data provide evidence that the Neb ‐cKO mouse model does not reproduce the large fatty infiltration typically observed in NEM patients.…”
Section: Discussionmentioning
confidence: 63%
“…Our results are in line with the small amount of fatty tissue infiltration in the hindlimb muscles (i.e., <5%) of two other NEM mouse models, whereas large fat infiltration has been reported in NEM patients. [27][28][29] Therefore, our MRI data provide evidence that the Neb-cKO mouse model does not reproduce the large fatty infiltration typically observed in NEM patients.…”
Section: Discussionmentioning
confidence: 80%
“…The soleus muscle was relatively normal on MRI. Histochemical aspects in that patient revealed nemaline bodies and type II fiber deficiency ( 12). Previous radiological hallmarks support that the gastrocnemius and tibialis anterior muscles are affected early in congenital nemaline myopathy.…”
Section: Discussionmentioning
confidence: 53%
“…However, muscle histochemistry was not described in that report (1 1). In another report (12) of an ambulatory case, MRI exhibited remarkable hyperintensity in the quadriceps femoris, caput medialis of the gastrocnemius and tibialis anterior muscles. The soleus muscle was relatively normal on MRI.…”
Section: Discussionmentioning
confidence: 89%